Temporomandibular disorders. Part 1: anatomy and examination/diagnosis. (February 2014) - Shaffer, Stephen M.; Brismée, Jean-Michel; Sizer, Phillip S.; Courtney, Carol A.
<x content-type="archive" xml:space="preserve">Abstract</x> Temporomandibular disorders (TMD) are a heterogeneous group of diagnoses affecting the temporomandibular joint (TMJ) and surrounding tissues. A variety of methods for evaluating and managing TMD have been proposed within the physical therapy profession but these sources are not peer-reviewed and lack updates from scientific literature. The dental profession has provided peer-reviewed sources that lack thoroughness with respect to the neuromusculoskeletal techniques utilized by physical therapists. The subsequent void creates the need for a thorough, research informed, and peer-reviewed source regarding TMD evaluation and management for physical therapists. This paper is the first part in a two-part series that seeks to fill the current void by providing a brief but comprehensive outline for clinicians seeking to provide services for patients with TMD. Part one focuses on anatomy and pathology, arthro- and osteokinematics, epidemiology, history taking, and physical examination as they relate to TMD. An appreciation of the anatomical and mechanical features associated with the TMJ can serve as a foundation for understanding a patient's clinical presentation. Performance of a thorough patient history and clinical examination can guide the clinician toward an improved diagnostic process.